Non-Born–Oppenheimer calculations of atoms and molecules - Cafiero, Mauricio; Bubin, Sergiy; Adamowicz, Ludwik (My University, 2003)
We review a recent development in high-accuracy non-Born–Oppenheimer calculations of atomic and molecular systems in a basis of explicitly correlated Gaussian functions. Much of the recent progress in this area is due to the derivation and implementation of analytical gradients of the energy functional with respect to variational linear and non-linear parameters of the basis functions. This method has been used to obtain atomic and molecular ground and excited state energies and the corresponding wave functions with accuracy that exceeds previous calculations. Further, we have performed the first calculations of non-linear electrical properties of molecules without the Born–Oppenheimer approximation for systems with more than one electron. The results for the dipole moments of such systems as HD and LiH agree very well with experiment. After reviewing our non-Born–Oppenheimer results we will discuss ways this method can be extended to deal with larger molecular systems with and without an external perturbation
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Non-Born–Oppenheimer calculations; atomic and molecular system